2018
DOI: 10.1161/atvbaha.117.309760
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 Promotes Neutrophil Infiltration and Tissue Injury on Ischemia–Reperfusion

Abstract: Our experimental data provide novel insights into the nonfibrinolytic properties of the fibrinolytic system and emphasize plasminogen activator inhibitor-1 as a promising target for the prevention and treatment of I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 56 publications
6
36
0
Order By: Relevance
“…In line with our hypothesis, pretreatment with RAP significantly inhibited F-actin polymerization and neutrophil migration in response to r-tPA, but not CXCL8. Of interest those results are in line with a previous report showing that blockade of LRP-1 prevents intravascular adherence and neutrophil recruitment within the ischemic tissue [ 29 ]. Furthermore, in the same work the authors found that exogenously administrated PAI-1 acts as an inflammatory mediator that guide circulating neutrophils to postischemic tissue through LRP-1 [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our hypothesis, pretreatment with RAP significantly inhibited F-actin polymerization and neutrophil migration in response to r-tPA, but not CXCL8. Of interest those results are in line with a previous report showing that blockade of LRP-1 prevents intravascular adherence and neutrophil recruitment within the ischemic tissue [ 29 ]. Furthermore, in the same work the authors found that exogenously administrated PAI-1 acts as an inflammatory mediator that guide circulating neutrophils to postischemic tissue through LRP-1 [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…Of interest those results are in line with a previous report showing that blockade of LRP-1 prevents intravascular adherence and neutrophil recruitment within the ischemic tissue [ 29 ]. Furthermore, in the same work the authors found that exogenously administrated PAI-1 acts as an inflammatory mediator that guide circulating neutrophils to postischemic tissue through LRP-1 [ 29 ]. In consideration of our results and the previously showed high affinity of tPA and PAI-1 towards LRP-1 when in complex [ 9 ], we cannot exclude that those observations were at least partially mediated also by tPA.…”
Section: Discussionsupporting
confidence: 90%
“…The subsequent profound hypofibrinolytic state at the end of transplantation is also in line with previous observations in adult and pediatric transplantation . Although PAI‐1 levels were elevated in patients at all time points, PAI‐1 levels did not fully explain the hypofibrinolytic status, and other factors, notably low plasminogen levels likely contribute . The persistent high levels of PAI‐1 and postoperative hypofibrinolytic state may be clinically relevant because increased PAI‐1 levels and prolonged CLT are associated with an increased risk of venous and arterial thrombosis .…”
Section: Discussionsupporting
confidence: 85%
“…It functions as the principal inhibitor of tissue-or urokinase-type plasminogen activator, and hence fibrinolysis, with additional nonfibrinolytic function recently discovered. [45][46][47] PAI-1 is mainly produced by the endothelium but is also secreted by other tissue types, such as adipose tissue. Elevated PAI-1 is a risk factor for thrombosis and atherosclerosis.…”
Section: Plasminogen Activator Inhibitor-1mentioning
confidence: 99%